Cultural Reproduction of Javanese Gamelan Creation - Wijaya, Mahendra; Pujihartati, Sri Hilmi (Advances in Social Sciences Research Journal, 2018)
This research aimed to find out the cultural reproduction of Javanese gamelan creation. Gamelan is an Indonesian orchestra composed mainly of tuned percussion instruments such as bamboo xylophones, wooden or metal chimes, and gongs. This reserach consisting of life attitude, work ethos, and skill of craftspeople in creation of Javanese gamelan. Cultural reproduction practice occurs in family, school/art institute/home industry environment and gamelan industry center community. This study employed naturalistic inquiry, describing the cultural reproduction of Javanese gamelan Creation naturally; the informants of research consisted of Empu (master craftsman) who produces gamelan, gamelan craftspeople, Javanese gamelan art figure, and Javanese gamelan users. The result of research revealed that life attitudes the Empu and the gamelan craftspeople had were: awareness of giving service to God, faith in God, being loyal to their job, submitting to the fate with gratitude, never being desperate, and having noble character. The work ethos of Empu and craftspeople included: hard work, high togetherness, carefulness, tolerance, high sense of belonging to the job, and mutual help. Meanwhile, gamelan creation skill included: membesot, menyingi, menempa, membabar, and melaras. Life attitude, work ethos, and skill of gamelan creation occurred through parents’ socialization from one generation to the next or from Empu to craftspeople in home industry. In industrial center community, gamelan gave Wirun villagers an identity as tough and reliable Empu and craftspeople. Keywords: Cultural Reproduction, Life Attitude, Work Ethos, Gamelan.